In Pursuit of “Islamic Art and Architecture” (American Journal of Islam and Society, 2009)
Books Reviewed: Richard Yeomans. The Art and Architecture of IslamicCairo. United Kingdom: Garnet Publishing, 2006; Doris Behrens-Aboseif.Cairo of the Mamluks: A History of the Architecture and Its Culture. UnitedKingdom: I.B. Tauris, 2007. GeorgeMichell. The Majesty ofMughalDecoration:The Art and Architecture of Islamic India. New York: Thames andHudson, 2007.Many people take it for granted that the blanket term Islamic art and architectureis sufficient to convey the vast production carried out in the name ofIslam; however, they often have a limited vision of what this term actuallyentails. Islam’s time span (fourteen centuries and counting) and geography(historically ranging from Spain to China) simply means that the art andarchitecture produced in its name deserves a more detailed and accountablepresentation of fact. In other words, it would be unthinkable for scholars touse a term like Christian art and architecture instead of such specific termsas Byzantine, Romanesque, and Gothic, each of which relates to a specifictime and place. Thus, the vocabulary of understanding the production of artand architecture in Islam’s name requires the use and understanding of clearterms and deserves specific publication and study ...